(untitled) (Acta herbologica, 2023)
The Editorial Board of “Acta herbologica” journal, in agreement with authors (Prijić Željana, Marković Tatjana, Radanović Dragoja, Jingqi Xue, Xiuxin Zhang, Gordanić Stefan, Mikić Sara, Dragumilo Ana, Čutović Natalija, Batinić Petar) of the paper “The effect of the year on the steppe peony´s morphological and ornamental traits” (Vol 32, No 1, p. 65-72, 2023) who pointed out the technical errors that occurred after the paper was published, made the decision to do the necessary corrections in accordance with the prescribed procedure. We apologize the authors for errors that occurred in published paper and thank them for assistance in detecting them. According to that, the appropriate correction was made.